A novel approach for designing nonwoven hybrid wound dressings: Processing and characterisation - UZUN, MUHAMMET (SAGE PUBLICATIONS INC, 2016)
The paper focuses on the development of novel absorbent nonwoven structures by using natural biodegradable carboxymethylcellulose (CMC), alginate and polylactic acid (PLA) fibres. These fibres have been blended and reinforced with synthetic hollow polyester (HPES), polypropylene (PP) and hollow viscose (HV) fibres. The main aim was to enhance the wicking properties of the structures for minimising the pooling of exudate and maceration. It is also aimed to enhance the integrity of structures to minimise the contamination of wounds due to loose fibres. The incorporation of PLA into wound dressings has been attempted for the first time and their functional properties have been studied. The single-fibre, blended and hybrid fabrics have been engineered. The results demonstrate that HPES reinforcement has a critical importance for CMC fabric in terms of wicking properties, tensile properties and air permeability. It has also been demonstrated that the contribution of PLA in the wound dressings is to enhance the properties such as absorbency, wicking, flexural rigidity and air permeability.
Keywords: Nonwoven wound dressings; carboxymethylcellulose (CMC); alginate; polylactic acid (PLA); hollow polyester (HPES); needlepunching; ANTIBACTERIAL